2020
DOI: 10.1002/maco.201911373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of corrosion behavior at elbow by array electrode and computational fluid dynamics simulation

Abstract: The present study focuses on the flow-accelerated corrosion (FAC) behavior of A106Gr.B steel at 90°elbow by electrochemical measurement and computational fluid dynamics (CFD) simulation. The FAC rates under turbulent flows with a velocity of 3 and 1.5 m/s were measured by an array electrode technique in a loop system. The experimental results reveal that the maximum FAC rate appears at the extrados of 90°elbow, consistent with the locations from the rupture of the carbon steel piping in the worst cases at elbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The macro-cell current is an important factor for steels subjected to an inhomogeneous flow condition. It is known that the inhomogeneous flow field usually occurs at the elbow, 3,21,23,28,31 reducer 12,30 and welded joint 18 of the pipeline and the surface of the ship hull or other large-scale steel structures, 17,34 which could lead to the non-uniform distribution of the local mass transfer rate and rust layer. Major anodic sites might concentrate at the local areas where lower mass transfer rate are registered.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The macro-cell current is an important factor for steels subjected to an inhomogeneous flow condition. It is known that the inhomogeneous flow field usually occurs at the elbow, 3,21,23,28,31 reducer 12,30 and welded joint 18 of the pipeline and the surface of the ship hull or other large-scale steel structures, 17,34 which could lead to the non-uniform distribution of the local mass transfer rate and rust layer. Major anodic sites might concentrate at the local areas where lower mass transfer rate are registered.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally found that the local areas where high FAC rates are registered are always coincide with the areas suffering high wall shear stresses or high mass transfer rates. 21,27,28,30 As a result, the study of localized FAC is well linked to the prediction of the local areas where high wall shear stress and high mass transfer rate are registered. However, Kitajima 33,34 claimed that serious FAC of the cast iron pumps preferred to occur at the local area around the shaft hole where the flow velocity and the wall shear stress were relatively low.…”
mentioning
confidence: 97%
See 3 more Smart Citations